Trajetórias sócio-educacionais de adultos surdos: condições sociais, familiares e escolares - Mendonça, Suelene Regina Donola (2007)
The aim of this study, whose field research was held in 2006, is to investigate the socio-educational trajectories of deaf adults with ages between 19 and 69 years old, from different social layers in Pindamonhangaba and Tremembé two municipal districts in São Paulo that have experienced school or not, but who are not there nowadays. We have tried to understand, from the own individuals or their relatives reports, how these trajectories were build, i.e., the marks, the singularities and the factors that have influenced them. The present investigation flows into studies developed by Bueno (1993, 1997, 2001, 2004, 2007), Soares (1999, 2004), Cukierkom (1996) and Oliveira (2007), which are based on the perspective that deafness is a biological distinctive mark, but that the social construction of the individual is determined by different factors, such as psychological, biological, social, environmental, political or economical that must be considered when we analyze the social destination of the individual. The theoretical basis of this study is the contribution of Bernard Charlot (2000), Bernard Lahire (1997, 2004) and Pierre Bourdieu (2003) in a way to understand the peculiarities that are present on the social relationships based on the cultural and social capital as well as their origins and their implications on the process of being a member of school and the individuals social destiny. The procedures used for data collect were the interviews with six deaf adults based on three fundamental orders their lives in the family, at school and in society. The analysis revealed to us that, besides the deafness mark, four other factors interfered on their trajectories: a) the origin capitals of the families as an important role on their lives at school, as well as on their possibilities of social insertion, but not the only one; b) the kind of school, the courses that were taken, the level they reached, their school experiences as an important role on the social insertion of deaf individuals, without defining their social destinies; c) the social relationships established by deaf individuals (based or not on their families and spouses) constituting important factors on the quality of their school trajectory and social insertion; d) the deafness mark must be considered an essentially adverse condition that cannot define the individuals destiny by itself